A secondary analysis of cortical atrophy and plasma amyloid β patterns in older patients with cognitive frailty undergoing elective surgery - Mörgeli, Rudolf; Borchers, Friedrich; Feinkohl, Insa; Piper, Sophie K.; Pischon, Tobias; Slooter, Arjen J.C.; Spies, Claudia; Wiebach, Janine; Winterer, Georg; Zacharias, Norman; Lammers-Lietz, Florian (BMC geriatrics, 2025)
Background The etiology of cognitive impairment in frailty may be related to age or to an independent neurodegenerative process, such as Alzheimer’s disease (AD). In this secondary analysis, we examine cognitive frailty in patients aged 65 and older undergoing elective surgery, and explore associations with aging- and AD-related cortical atrophy patterns and amyloid β (Aβ) concentrations. Methods Cognitive frailty (CF) was defined as the co-occurrence of (pre-)frailty and cognitive impairment (CI). Cognitive performance was assessed using the MMSE and the Cambridge Neuropsychological Teste Automated Battery (CANTAB), while frailty was assessed with a modified version of Fried’s frailty phenotype. Aging- and AD-related cortical atrophy patterns were derived from T1-weighted MRI using Freesurfer software. MRI patterns and plasma concentrations of Aβ species 40 and 42 (including Aβ 42/40 ratio) were compared to physically robust, cognitively unimpaired patients using multiple regression analyses and presented as regression coefficient b with 95% confidence intervals. Results MRI data of N = 489 patients ( N = 251 with frailty, N = 15 with CI, N = 43 with CF) and plasma Aβ concentrations of N = 786 patients ( N = 400 with frailty, N = 20 with CI, N = 101 with CF) were analyzed. Cognitive frailty was associated with both aging-related and AD-related MRI signatures (b age =-0.070 [-0.113; -0.028], b AD =-0.069 [-0.118; -0.020]). Amyloid β42 was significantly lower in frail patients (b=-0.14 [-0.29; -0.01]), while β42/β40-ratio was lower in patients with frailty (b=-0.11 [-0.21; -0.01]) and cognitive frailty (b=-0.015 [-0.28; -0.03]). Conclusion Our results suggest that atrophy in aging- and AD-related cortical regions is associated with cognitive frailty. Plasma amyloid β42/β40-ratios were significantly lower in patients with frailty and cognitive frailty, suggesting that (pre-)frailty in general, rather than cognitive frailty specifically, is associated with AD-like changes. Hence, AD-related pathology seems to be associated with cognitive frailty, but the available data is not sufficient to indicate shared pathomechanisms between AD and cognitive frailty. Trial Registration ClinicalTrials.gov. Identifier NCT02265263, Date October 15th, 2014.